Growth Performance, Some Carcass Traits and Biochemical Parameters of Ross 308 Broilers Under Commercial Farming Conditions in Northeastern of Libya - Mabruka Sitmo; Omar Meriz; Fares Aboushnaf; Najwa Ismaael (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Assessment of productivity of exotic strains of broilers should be periodically carried out to define their requirements and optimize productive efficiency. The growth performance, some carcass characteristics and blood parameters of Ross 308 broiler chickens under traditional rearing conditions in northeastern of Libya were investigated. Methods. The body weight (BW) and feed consumption were weekly measured, and average daily feed intake (ADFI), average daily gain (ADG), and gain: feed ratio (FCR) were calculated. At 35 days of age the final body weight, carcass characteristics and blood parameters of broilers were determined. Results. The results revealed that at 35 days of rearing, the chickens reached the mean final body weight of 1756.26 g, the eviscerated carcass weight averaged 957.1 g, and slaughter yield was 60.8%. The ADFI, ADG, and FCR were 81.95 (g/b/day), 48.62 (g/b/day) and 1.68, respectively. Mean internal organ weights were in the range reported previously for Ross 308 broilers. Of the serum biochemical parameters tested, the mean ALP and AST levels were higher than the values reported previously in literature for Ross 308 broiler chickens which could reflect pathological changes in broilers reared under traditional and commercial conditions in study area. Conclusion. Ross 308 chickens examined under commercial conditions did not attain final body weight of 2 kg and slaughter yield of 70% as productive performance targets in broiler production system which could reflect improper practice managements applied to broiler through the entire rearing period.